Meningeal tuberculoma mimicking a brain tumor - Bravo-Tsri, Akoli Eklou Baudouin (Radiol Case Rep, 2020)
Meningeal tuberculoma is one of the most serious sites of tuberculosis. Its incidence varies depending on the geographical area, rare in Western countries and frequent in developing countries where it represents 5% to 10% of intracranial masses. We report the case of a 21-year-old male patient with no particular medical history from Africa and living in Europe for more than a year, is hospitalized for an isolated inaugural, generalized, afebrile seizure in whom the scanner and cerebral magnetic resonance imaging (MRI) revealed a meningeal mass with significant glove finger edema suggesting a primary brain tumor. Surgical excision and anatomopathological analysis of the excisional piece allowed the diagnosis of tuberculoma. Meningeal tuberculoma is a source of diagnostic error because its clinical and radiological expression can mimic a brain tumor. This is an etiology that should not be ignored in the face of a meningeal mass in any subject coming from or living in a region with a high endemic tuberculosis.